Restless Legs Syndrome-associated intronic common variant in Meis1 alters enhancer function in the developing telencephalon - Spieler, Derek; Kaffe, Maria; Knauf, Franziska; Bessa, José; Tena, Juan J.; Giesert, Florian; Schormair, Barbara; Tilch, Erik; Lee, Heekyoung; Horsch, Marion; Czamara, Darina; Karbalai, Nazanin; et al. (Genome Research, 2014)
Genome-wide association studies (GWAS) identified the MEIS1 locus for Restless Legs Syndrome (RLS), but causal single nucleotide polymorphisms (SNPs) and their functional relevance remain unknown. This locus contains a large number of highly conserved noncoding regions (HCNRs) potentially functioning as cis-regulatory modules. We analyzed these HCNRs for allele-dependent enhancer activity in zebrafish and mice and found that the risk allele of the lead SNP rs12469063 reduces enhancer activity in the Meis1 expression domain of the murine embryonic ganglionic eminences (GE). CREB1 binds this enhancer and rs12469063 affects its binding in vitro. In addition, MEIS1 target genes suggest a role in the specification of neuronal progenitors in the GE, and heterozygous Meis1-deficient mice exhibit hyperactivity, resembling the RLS phenotype. Thus, in vivo and in vitro analysis of a common SNP with small effect size showed allele-dependent function in the prospective basal ganglia representing the first neurodevelopmental region implicated in RLS.